2018
DOI: 10.3389/fpsyg.2018.02016
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Activity-Based Flexible Office Design on Teamwork

Abstract: This three-wave longitudinal interview study (time lag: 12 and 18 months) investigates the impact of working in an activity-based flexible office (A-FO) on processes within and across teams (i.e., communication, trust, cohesion, and collaboration) and team management. Based on a new theoretical framework on benefits and risks of A-FOs (A-FO-M; Wohlers and Hertel, 2017), we conducted interviews with 25 employees of an in-house training institute who recently switched from single cell or shared offices to an A-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 71 publications
2
35
1
1
Order By: Relevance
“…Explanations for this could be found in the interviews where employees described positive side-effects of the relocation, such as having stimulated meetings and interacting with colleagues from different departments. The effects on team collaborations in ABWs have also been shown in previous studies, e.g., [33].…”
Section: Methods Discussionsupporting
confidence: 80%
“…Explanations for this could be found in the interviews where employees described positive side-effects of the relocation, such as having stimulated meetings and interacting with colleagues from different departments. The effects on team collaborations in ABWs have also been shown in previous studies, e.g., [33].…”
Section: Methods Discussionsupporting
confidence: 80%
“…Another limitation is that the data was collected from only one organisation, which limits the generalisation of the results to other organisations and work contexts. A-FO's configuration and their implementation can differ from one organisation to another (Wohlers and Hertel 2018), and this should be accounted for in future studies. Furthermore, some previous studies called for exploring the mechanisms behind the effects of the work environment in general.…”
Section: Limitations and Suggestions For Future Studiesmentioning
confidence: 99%
“…The second largest cluster (numbered as #1) has 31 members and was labelled as the longitudinal effect by LLR. Moreover, the most active citer to cluster #1 is Wohlers and Hertel (2018), which analysed the longitudinal effects of activity-based flexible office design on teamwork. It was found that cluster label by LLR is influenced by the title of the most citer paper to the cluster.…”
Section: Figure 6 Timeline View Of Cocitation Referencesmentioning
confidence: 99%
“…The second-ranked article, with citation counts of 13, is de Menezes and Kelliher (2011) also in Cluster #0. Two references (Appel-Meulenbroek et al, 2011;Yin, 2009) were ranked third because they have the same citation counts of 9, and they are from the same Cluster #1. The first reference (Kelliher & Anderson, 2010) entitled "Doing more with less?…”
Section: Figure 6 Timeline View Of Cocitation Referencesmentioning
confidence: 99%
See 1 more Smart Citation